Creatine supplementation: bioavailability and effects on physical and cognitive performance - Gajda-Bathelt, Monika; Kwaterska, Katarzyna; Adasiewicz, Julia; Kutyłowska, Agata; Kutyłowski, Karol; Kuna, Paweł Jan; Chojniak, Alicja Katarzyna; Benecka, Agnieszka; Janawa, Kamil; Tomaszek, Michał (Quality in Sport, 2025)
Creatine supplementation is a well-established approach for improving outcomes in high-intensity exercise, yet the impact on cognitive function and the bioavailability of different creatine forms remain under active investigation. In this paper we summarize evidence on creatine bioavailability and its effects on physical and cognitive performance. Creatine monohydrate (CrM) is the gold-standard form, reliably increasing muscle phosphocreatine (PCr) stores and enhancing strength, power, sprint ability and fat-free mass. Creatine supplementation paired with resistance training enhances lean tissue mass and muscular strength in both younger and older individuals. Creatine also delays fatigue in high-intensity endurance sports and improves recovery during bouts of intermittent activity. Cognitive studies report modest benefits of creatine on memory and processing speed, particularly among older adults. Subgroup analyses show that vegetarians and elderly achieve greater creatine levels and cognitive benefits than omnivores and younger people. Side effects are minimal, except for minor gastrointestinal discomfort or weight gain from fluid retention. In summary, creatine monohydrate is highly bioavailable and consistently improves strength and power outcomes, with emerging evidence for cognitive enhancement. Evidence on alternative forms is limited, thus further research is needed to clarify their bioavailability and long-term safety.